1865. Analysis of National Surveillance Data to Support Case Definition Revisions for Multisystem Inflammatory Syndrome in Children (MIS-C), United States, February 2020–April 2022. (15th December 2022) - Campbell, Angela P; Miller, Allison D; Yousaf, Anna R; Lee, Ellen H; Lim, Sarah; Brown, Catherine M; Oster, Matthew; Abrams, Joseph; Lindsey, Katherine; Wu, Michael J; Cato, Shana Godfred; Ermias, Belay; et al.
Abstract: Background: Classification of MIS-C, COVID-19, and other pediatric inflammatory conditions is challenged by phenotypic overlap and absence of diagnostic laboratory evidence. Due to public health need and based on limited data from early cases, CDC developed a necessarily broad MIS-C surveillance case definition in May 2020. Studies have since shown that some criteria do not distinguish between MIS-C and other conditions and may contribute to misclassification. To inform planned revision to the CDC definition, we evaluated the impact of narrowing these criteria on case inclusion in national MIS-C surveillance. Methods: Of state and local health-department reported cases meeting the current MIS-C case definition as of 04/14/2022, we describe the proportion that met revised criteria under consideration including fever duration, C-reactive protein (CRP) elevation using a defined cutoff, and organ involvement represented by specific criteria. We also evaluated cases identified using potential combinations of revised criteria. Results: Of 8, 096 MIS-C cases fulfilling the original case definition, 6, 332 (78%) had sufficient data for evaluation of criteria. Of these, 96% had fever for ≥2 days and 94% had a CRP ≥ 3.0 mg/dL (Table 1). Cardiac involvement defined by key features of MIS-C was present in 84% of cases (62% if BNP/proBNP elevation was excluded); 43% had shock. Dermatologic, gastrointestinal (GI) and hematologic involvement were present in 75%, 89% and 37% of cases, respectively. Neurologic (excluding headache), renal, and respiratory involvement were present in 16%, 20%, and 63% of cases, respectively. The number of cases with ≥ 2 of cardiac (without BNP/proBNP elevation), shock, dermatologic, GI, or hematologic involvement was 5, 733 (91%). SARS-CoV-2 testing results are shown in Table 2. Conclusion: The CDC MIS-C case definition is intentionally broad. Using national surveillance data, we evaluated case inclusion under narrower criteria, prioritizing features of MIS-C that distinguish it from similar pediatric inflammatory conditions. A surveillance case definition may not capture all cases and is not intended to replace clinical judgment. We plan to assess additional criteria combinations, describe potentially excluded cases, and incorporate findings into a revised definition. Disclosures: All Authors : No reported disclosures.